EFEKTIVITAS PELAKSANAAN BIMBINGAN TERHADAP KLIEN PEMBEBASAN BERSYARAT DALAM MEWUJUDKAN REINTEGRITAS SOSIAL - Jaja Suteja Choirudin (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2018)
One of the activities in the series of law enforcement system activities is carried out by the Balai Pemrakrakatan (BAPAS) which is part of the prison system of criminal prison system or sub-system of justice. However, the existence and role of the Penitentiary (BAPAS) is often ignored or even unknown to other sub-systems in the legal system in Indonesia. In this study the approach used by researchers is a qualitative / naturalistic approach with the source of the data taken from information and interviews with the head of BAPAS, community supervisors and parole clients in the Cirebon Class I Correctional Center. While the data collection techniques are through observation, in-depth interviews and documentation studies. From the results of interviews with the head of the Cirebon Class I BAPAS, community supervisors and parole clients, produced a research result that the guidance and counseling carried out by the Cirebon Class I BAPAS could be said to be quite good or could run effectively. Although still finding various obstacles, among others; the reach of the working area is too broad, the availability of the quantity of Community Guidance HR is still lacking, the lack of budget, the lack of technical training that is carried out, the lack of infrastructure facilities that support the implementation of guidance and still not optimal support from the community. The conclusion of this study shows that the level of effectiveness of the implementation of guidance on parole clients in realizing social reintegration has been running effectively, both by the way clients come directly to BAPAS and community supervisors who directly meet each client's home (home visit).